The Security Dilemma and the Prevailing Trend of the Arms Race in the Middle East throughout 2020-2022 - Wibowo, Prihandono; Hapsari, Renitha Dwi; Ascha, Muchammad Chasif (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This research aims to find the causes of the arms race in the Middle East region from 2020 to 2022. The justification for the problem is that although from 2020 to 2022 there is a tendency for reconciliation of relations between countries in the Middle East, the arms race still continues in the region. In addition, military exercises conducted by the United States, Israel, and Gulf Arab states are getting more intense. This paper uses the conception of security dilemma in explaining the causes of the arms race trend in the Middle East region. The method used by this paper is qualitative by analyzing statements, news, and official documents from related Middle Eastern countries. This paper finds that mistrust between Middle Eastern countries, especially between Iran, Israel, and several Arab countries, causes tense relations between these actors. Each country increased its military power in response to the uncertain situation. Some Arab countries are strengthening their defense systems to counter Iran, which is perceived as a common threat. Iran is perceived by Israel and some Arab countries as an offensive country. Some Arab countries also normalized with Israel and formed strategic alliances with the Zionist state. In contrast, Iran continues to strengthen its military power because it has no trust in Israel and Arab countries. In conclusion, the conception of security dilemma can explain the distrust between actors in the Middle East region. As a result of this distrust, an arms race between countries occurs.